Establishing arbitrariness - Phillips, S (Refugee Studies Centre, University of Oxford, 2013)
The majority of provisions in the international human rights law instruments that deal with deprivations of liberty contain the term ‘arbitrary’, yet there is no clear definition of what this entails; understanding it requires awareness of the different factors affecting how individual deprivations of liberty are examined and understood